Psykiatrisk vård för fängelsedömda - Gunnar Holmberg; Anders Forsman; Martin Grann; Lars Erik Ingerloo; Stefan Skagerberg; Lis Somander (Nordisk Tidsskrift for Kriminalvidenskab)
See abstract in article.